Parry-Romberg Syndrome with a Clinically Silent White Matter Lesion - Okumura, A.; Ikuta, T.; Tsuji, T.; Kato, T.; Fukatsu, H.; Naganawa, S.; Kato, K.; Watanabe, K. (American Journal of Neuroradiology, 2006)
SUMMARY: We performed a detailed neuroimaging study in a patient with Parry-Romberg syndrome. Proton MR spectroscopy demonstrated normal spectral patterns, though conventional MR imaging revealed high-intensity areas in the entire white matter in the left hemisphere. Single-photon emission tomography showed increased perfusion in the cortex of the affected hemisphere. Pyramidal tracts and optic radiations were preserved on diffusion tensor tractography. We will correlate these neuroimaging findings with normal psychomotor development in our patient.